Mechanisms of tumor necrosis factor-α and interleukin-6 induction during human liver transplantation - Gerhard Hamilton; Sonja Vogel; Reinhold Fuegger; Franz X. M. Gnant (Mediators of Inflammation)
In human orthotopic liver transplantation (LTX) intraoperative elevations of TNF-α (> 100 pg/ml) and IL-6 (>800 pg/ml) have been found to correlate with early post-operative rejections and infections respectively. In this study the possible mechanism responsible for the induction of these cytokines has been investigated during liver allografting in 38 recipients. Intraoperative elevations of TNF-α (> 100 pg/ml) were detected in the majority of pre-transplant endotoxin positive recipients (8/12, > 10 endotoxin units/ml), the patients turning endotoxin positive until the end of grafting (3/5), and in a subgroup (6/21 patients), apparently endotoxin negative for the whole operation. Therefore endotoxin (ET) seems to stimulate release of TNF-α in approximately 50% of the patients, whereas sensitized Kupffer graft cells or immediate allograft reactivity of the host are likely to account for the remaining TNF-α positive cases. Elevations of IL-6 > 800 pg/ml) were found in approximately 50% of the TNF-α positive cases, indicating partially independent regulatory pathways for IL-6 induction in the TNF-α negative patients. In agreement with a previous study, 11/13 (85%) of the intraoperative TNF-α positive recipients rejected their grafts within the first 10 days post-operatively. These data demonstrate that ET/infection associated as well as ET independent/reperfusion associated intraoperative TNF-α elevations, promote the initiation of allograft rejection in human liver transplantation. The transient and low endotoxaemia caused by the liver grafting procedure performed without veno-venous bypass seems to be of minor importance in the intraoperative induction of TNF-α.